(3aJM GdLdjd aj TQM eNJUQ Ndjds - (3eMeO Hf EHQGgje GdJJGFi , CHh YHO Gddg TeS GdOjfs; (3Ndjd Hf ESMGb Hf ehSi, VjGA GdOjf GdoLrfpOj GdeGdcj GdeUQj,J (B776 (3g` s
(3ChdgG (B:s
(3JHOC H` HGH GdRcGI (B: (3gPG gh GdQHY GdKGfi , hGdRcGI hGdPcjI dZI GdPHM , hbjd (B: (3GUdgG GdJeGe HYfi PcjJ GdPHjMI (B: (3GJeJ PHMgG , hPcjI GdfGQ , CJeeJ EjbGOgG s
(3BNQgG (B:s
(3hbjd Ef GSJbQJ LejY CReGfgG RLHJ dgG GdfabI , ceG JLH ddMGed dCLd GdMed , hEf de JSJbQ ai CReGfgG , ajLH eG jbOQg Cgd GdeYQaI hGdgd CYde hGdMeO ddg hcai s
(3GdfSNI HgG MhGTs
(3fSNI bOjeI LOkGs
(3HYV cdeGJgG HGdMeQI s
(3hHgG fXGe GdJYbjHI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdeGdcjs